THE ROLE OF FRACTALKINE AS A MARKER OF THE INFLAMMATORY ACTIVITY AT COMBINED RESPIRATORY CARDIAC PATHOLOGY - A. Kh. Akhmineeva; O. S. Polunina; I. V. Sevostyanova; L. P. Voronina (Кубанский научный медицинский вестник)
In this research, the authors established the role of fractalkine as a marker of inflammatory activity at concomitant respiratory cardiac pathology, which flows with potentization of systemic inflammatory reactions. We found that in patients with arterial hypertension (AH), and in patients with chronic obstructive pulmonary disease (COPD) activation of systemic inflammation is occured, more expressed in patients with COPD. At the same time, the development of AH in patients with COPD is not accompanied by increasing of fractalkine levels, in comparison with mononozology. When combined COPD with coronary heart disease (CHD) has increased production of fractalkine compared with mononozology (COPD, CHD). The combination of COPD+CHD more adversely in relation to the systemic inflammatory activation.